Persilangan 4 varietas kedelai (Glycine max L.) dalam rangka perakitan kedelai tahan kering - Frendi Heri Utomo; Budi Adi Kristanto; Florentina Kusmiyati (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
The purpose of this research was to study dialel crossing of 4 soybean varieties in order to get drought resistant varieties. The research used Completely Randomized Design with six crossing combination : Dering x Grobogan, Grobogan x Dering, Dering x Detam, Detam x Dering, Dering x Devon, and Devon x Dering. Each combination was repeated five times. Parameters observed were percentage of fertilization, number of seeds in pods, long of pods, weight of 10 seeds. Parameters were analyzed descriptively and heterosis was calculated. The research results showed that crossing between dering and devon had the highest percentage of fertilization. Crossing between dering and grobogan improved number of seed in pod, long of pods and weight of 10 seeds. The highest heterosis of seed number in pod, long of pods and weight of 10 seeds were resulted from crossing dering x devon, Dering x Grobogan, Grobogan x Dering, respectively. Keywords : Crossing, genotype soybean, fist population